More than a headache—somatic and mental symptom burden in spontaneous intracranial hypotension before and after surgical treatment - Volz, Florian; Lahmann, Claas; Wolf, Katharina; Fung, Christian; Shah, Mukesch Johannes; Lützen, Niklas; Urbach, Horst; Zander, Charlotte; Beck, Jürgen; El Rahal, Amir (Frontiers in Neurology, 2024)
Introduction Patients with spontaneous intracranial hypotension (SIH) frequently present with several symptoms and impaired mental health. This study systematically investigates the somatic and mental symptom burden of SIH and the effect of surgical treatment. Methods In this single-center retrospective study, patients with surgical closure of a spinal cerebrospinal fluid leak between September 2022 and July 2023 completed the Somatic Symptom Scale (SSS-8), the Somatic Symptom Disorder – B Criteria Scale (SSD-12), and the Patient Health Questionnaire (PHQ-8) preoperatively and three and 6 months postoperatively. Results Fifty-seven patients were included. All three scores showed clearly pathological values before surgery (SSS-8: 12 [IQR 6.5–16], SSD-12: 26 [IQR 19.5–33.5], PHQ-8: 11 [IQR 6.5–15]) representing a high somatic symptom burden and relevant current depression. After surgery, there was a significant and sustainable improvement (SSS-8: 8 [IQR 3–11.75], SSD-12: 12.5 [IQR 5–21.75], PHQ-8: 4.5 [IQR 2–9], p < 0.001, respectively) that exceeded the minimal clinically important difference for every score. Conclusion SIH presents with high somatic and mental symptom burden. Surgical treatment leads to a relevant improvement of somatic and depressive symptoms. However, even after surgical success some patients still exhibit elevated depressive scores. Depressive symptoms might be added to the typical symptomatology of SIH.